"The Logic of Care" - Parents' perceptions of the educational process when a child is newly diagnosed with type 1 diabetes - Jönsson Lisbeth; Hallström Inger; Lundqvist Anita (BMC, 2012)
Abstract Background The number of new cases of type 1 diabetes mellitus (T1DM) has increased substantially in recent years and it is now one of the most common long-term endocrine disorders in childhood. In Sweden the child and family are hospitalised in accordance with the national guidelines for one to two weeks at diagnosis. The purpose of this study was to describe parents' perceptions of the educational process when their child is newly diagnosed with T1DM. Methods Qualitative interviews were performed in the south western part of Sweden with ten mothers and eight fathers of children, diagnosed with T1DM, at three to six months after they had received the diagnosis. The interviews were analysed using deductive content analysis and Mol's philosophical theory. Results The results show that almost all parents had experienced the educational process as being satisfactory. However, most parents felt that the teaching needed to be adapted to the individual families and to help them to learn to live with diabetes in their everyday lives. Rather than merely teaching according to a fixed schedule and cramming knowledge, the education should be parent-centered and provide time for grief and shock. There should also be a greater emphasis on why certain things should be done rather than on what should be done. The routines learned at the hospital made the efforts to be good parents managing the child's disease, and continuing to lead a normal family life, a difficult task. Conclusions In order to optimize the educational process for families with children newly diagnosed with T1DM an increased focus on the families' perceptions might be helpful in that this could lead to further revelations of the educational process thus making it more understandable for the family members involved.